PENGARUH KONFLIK PERAN GANDA, STRESSOR PEKERJAAN DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA POLISI SATUAN RESERSE DAN KRIMINAL POLRES MERANGIN - Krisna Putra Octodi; Almasdi Almasdi (Institut Agama Islam Negeri Kerinci, 2022)
Purpose: This study aims to examine the effect of (1) dual role conflict, Job stressors on police and The work environment on the job satisfaction of the police of the Merangin Police and Criminal Investigation Unit. Design/methodology/approach: The population in this study were all 32 police officers from the Merangin Police and Criminal Investigation Unit. And the technique of determining the number of samples taken as respondents with this sampling technique using the total sampling technique (whole sample). The reason for taking total sampling is because according to the total population is less than 100, the entire population is used as a research sample . Findings: The results of this study indicate that (1) dual role conflict has a negative effect on police job satisfaction at the Bukittinggi Police. (2) Job stressors have a negative effect on job satisfaction of the police of the Merangin Police and Criminal Investigation Unit. (3) The work environment has a positive influence on the job satisfaction of the Merangin Police Criminal and Investigation Unit. (4) Multiple role conflicts, stressors and the work environment together have a significant effect on police job satisfaction at the Merangin Police and Criminal Investigation Units. Research implications: The results of this study are expected that by having high job satisfaction, the police can provide maximum service to the community, especially in the Merangin Police Criminal and Investigation Unit.